1995
DOI: 10.1007/bf03010711
|View full text |Cite
|
Sign up to set email alerts
|

Placental transfer of lidocaine hydrochloride after prolonged continuous maternal intravenous administration

Abstract: We treated a patient with arrhythmia during pregnancy with prolonged intravenous administration of lidocaine hydrochloride. This was a case of twin-to-twin transfusionLidocaine is widely used for maternal analgesia during labour and sometimes for the treatment of arrhythmia in pregnant women. There are many reports of human placental lidocaine transfer after brief administration following maternal epidural, spinal, caudal, paracervical or pudendal analgesia during labour. However, for continuous maternal lidoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Transport of lidocaine through the placenta has been reported. In our study, the F/M plasma concentration ratio of lidocaine at the time of delivery (0.52 ± 0.07) was similar to the reported F/M ratio values after the perineal and systemic administration of lidocaine (0.46 and 0.52, respectively), with no neonatal adverse effects [7,24]. We recorded no difference in neonatal outcome, as assessed by Apgar scores, NACS, and blood gas analyses, with the perioperative use of i.v.…”
Section: Discussionsupporting
confidence: 90%
“…Transport of lidocaine through the placenta has been reported. In our study, the F/M plasma concentration ratio of lidocaine at the time of delivery (0.52 ± 0.07) was similar to the reported F/M ratio values after the perineal and systemic administration of lidocaine (0.46 and 0.52, respectively), with no neonatal adverse effects [7,24]. We recorded no difference in neonatal outcome, as assessed by Apgar scores, NACS, and blood gas analyses, with the perioperative use of i.v.…”
Section: Discussionsupporting
confidence: 90%
“…Animal studies to determine the physiologic mechanism for the nonfunctional changes have demonstrated that G628S channels can conduct Na + , but this can be blocked by both intracellular and higher than physiologic extracellular K + . Thus, lidocaine, a sodium channel blocker that is established treatment for LQT3 (a sodium channel mutation), may be successful in treating ventricular arrhythmias associated with this particular mutation.…”
Section: Discussionmentioning
confidence: 99%
“…At 29 0/7 weeks, we added lidocaine (1 mg/kg of maternal weight followed by 1 mg/min continuous infusion) to the treatment regimen. Lidocaine, a sodium channel blocking agent, was chosen because of data suggesting that it shortens the QT interval and normalizes repolarization across the myocardium . At a dose of 1.5 mg/min (maternal serum level 2.0 μg/ml), the fetal rhythm converted to sustained sinus bradycardia (fetal heart rate 110 bpm).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…This influence could be related to differences in degree of stress between vaginal and cesarean delivery [6,7] and to the fact that the drugs used in cesarean section cross the placenta and reach circulation in the fetus [8][9][10].…”
Section: Introductionmentioning
confidence: 99%